216 Does Aortic Stenosis Effect Platelet Closure Time and Von Willebrand Factor Activity?. (3rd June 2016) - Choudhary, Ferrah; Kirby, Richard; Peter, Christina; Henderson, Robert
Abstract : Background: Abnormal platelet function is associated with increased bleeding risk. Limited evidence suggests that platelet dysfunction is a cause of bleeding in patients with aortic stenosis (AS). Method: 40 patients with degenerative AS underwent detailed haematological assessment. Platelet closure time (PCT) in seconds, was measured from a citrated blood sample by a PFA 100 benchtop analyser. In the presence of standardized flow conditions and collagen and ADP agonists, high shear rates are created, leading to aggregation of platelets and subsequent occlusion at the aperture site. The PCT is recorded as the time taken for the aperture occlusion to develop. Mean platelet volume (MPV) and platelet count (as per the impedance method) were measured from an EDTA sample by a XE2100 analyser. Von Willebrand factor activity was assessed with collagen binding assay (vWF:CB). Each patient completed a questionnaire to document use of antiplatelet therapy (with aspirin/clopidogrel) and bleeding events (using the ISTH bleeding questionnaire). Results: Of the 40 patients, 8 had mild AS, 23 moderate AS and 9 severe AS. The average age was 74.9 years (range 39–97) and 47.5% were male. All patients had a normal MPV. A low platelet count was noted in 3 patients and all had an associated prolonged PCT. VWF activity was abnormal in 60% (n = 24: 5 mild AS, 12 moderate, 7 severe) but there was no correlation with AS severity. Overall, 25 patients (62.5%) had a prolonged PCT, including 5 patients (1 mild AS, 1 moderate AS and 3 severe AS) with significant bleeding events (2 patients with gastrointestinal bleeding and 3 with epistaxis). All bleeding events occurred within 3 months of the haematological assessment and in 2 cases were ongoing when the patient completed the questionnaire. Only 1 patient with normal PCT had significant bleeding. A higher PCT was associated with more severe AS (p = 0.002, Table 1) and with the use of antiplatelet therapy (p = 0.043). Patients without antiplatelet therapy (n = 18) had a mean PCT of 126.5 (SD 36.94) vs patients on antiplatelet therapy, mean PCT of 174.5 (SD 82.15). There was no statistically significant relationship between PCT and vWF activity (p = 0.16). Conclusion: This study demonstrates that PCT is associated with AS severity but this association may be partly explained by an excess of antiplatelet therapy use in patients with severe AS. In this small sample there was no association between platelet closure time and abnormal vWF activity. Ongoing studies will explore these findings in greater detail.